2018
DOI: 10.1021/acsanm.8b00634
|View full text |Cite
|
Sign up to set email alerts
|

Multisensing Capability of MoSe2 Quantum Dots by Tuning Surface Functional Groups

Abstract: Several distinct surface-functionalized molybdenum diselenide (MoSe 2 ) quantum dots (QDs) were developed as chemosensors based on the fluorescent probe. The carboxylic-, amine-, and thiol-functionalized MoSe 2 QDs (MoSe 2 /COOH, MoSe 2 /NH 2 , and MoSe 2 /SH) were synthesized by tuning their surface with thiol-containing capping agents. These MoSe 2 / COOH and MoSe 2 /NH 2 QD sensors were implemented for the highly selective and sensitive detection of copper ion (Cu 2+ ) and 2,4,6-trinitrophenol (TNP) with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 80 publications
1
26
0
Order By: Relevance
“…The fluorescence response pattern was created by comparing the fluorescence intensity of all the quantum dots before and after addition of the analytes and termed as I 0 – I 1 (Figure S4a). Insignificant quenching of the fluorescence intensity of all the quantum dots by NACs (except PA and dinitrosalicylic acid (DNSA)) is also in agreement with previous reports. When the datasets corresponding to three channel × nine NACs × six repeats (three channel represents three quantum dots) were subjected to LDA, the quality of 2D LDA score plot was not suitable for discrimination (Figure a). PA and DNSA were well-separated in the LDA score plot, while other NACs showed significant overlapping (Figure a).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The fluorescence response pattern was created by comparing the fluorescence intensity of all the quantum dots before and after addition of the analytes and termed as I 0 – I 1 (Figure S4a). Insignificant quenching of the fluorescence intensity of all the quantum dots by NACs (except PA and dinitrosalicylic acid (DNSA)) is also in agreement with previous reports. When the datasets corresponding to three channel × nine NACs × six repeats (three channel represents three quantum dots) were subjected to LDA, the quality of 2D LDA score plot was not suitable for discrimination (Figure a). PA and DNSA were well-separated in the LDA score plot, while other NACs showed significant overlapping (Figure a).…”
Section: Resultssupporting
confidence: 89%
“…They can be easily synthesized through ball milling, sonication, solvothermal process, etc. The major challenge for most of the quantum dots is the higher selectivity toward tri-nitro compounds like picric acid (PA) and trinitrotoluene (TNT) compared to other mono- or di-nitro compounds since tri-nitro compounds are highly electron-deficient as compared to other NACs and can consequentially accept electrons easily from electron-rich quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…[204] To achieve lower toxicity and higher detection performance, researchers have designed fluorescence sensors based on QDs derived from different layered materials, such as BP, TMDs, MXenes and h-BN. [136,167,[205][206][207] Importantly, different fluorescence quenching mechanisms, such as inner filter effect (IFE), photoinduced electron transfer (PET) and fluorescence resonance energy transfer (FRET), can be achieved by appropriate tuning of the QDbased sensing system. Among them, the IFE, which originates from the overlap between the excitation/emission spectrum of the fluorescers and the absorption spectrum of the absorbers, was reported to have a very low detection limit and high sensitivity.…”
Section: Heavy Metal Ion Detectionmentioning
confidence: 99%
“…A similar effect can be achieved by the incorporation of different surface functional groups or element doping. [206,211] Xu et al demonstrated a more practical Cu 2+ fluorescence probe based on BP QDs, which can be used in both aqueous and organic solutions. [211]…”
Section: Heavy Metal Ion Detectionmentioning
confidence: 99%
“…The coordination at S vacancies could be further applied to other kinds of TMDs, including WS 2 , TaS 2 , MoSe 2 , Sb 2 Te 3 , In 2 Se 3 , etc . This strategy might pave the way to realize various multifunctional TMDs‐based hybrid nanostructures.…”
Section: Coordination‐driven Assembly Based On Tmdsmentioning
confidence: 99%